2019
DOI: 10.3390/ijerph16020194
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and Faecal Incontinence: Point Prevalence and Predictors in a University Hospital

Abstract: Incontinence is common and associated with adverse outcomes. There are insufficient point prevalence data for incontinence in hospitals. We evaluated the prevalence of urinary (UI) and faecal incontinence (FI) and their predictors among inpatients in an acute university hospital on a single day. Continence status was recorded using the modified Barthel Index (BI). Baseline characteristics, Clinical Frailty Scale (CFS) and ward type were recorded. In all, 435 patients were assessed, median age 72 ± 23 years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 27 publications
3
35
0
2
Order By: Relevance
“…Rather, these sick and often elderly individuals are dependent on continence aids, adult diapers, sanitary pads and nursing cleanup; this results in fecal matter from these individuals being disposed into biohazard solid waste. Accordingly, wastewater-based sampling could miss between 10-20% of patients in general hospital patients ( Condon et al, 2019 ; Toba et al, 1996 ). This proportion is expected to be even higher in intensive care units where immobilization necessitated through ventilatory support further heightens toileting assistance requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, these sick and often elderly individuals are dependent on continence aids, adult diapers, sanitary pads and nursing cleanup; this results in fecal matter from these individuals being disposed into biohazard solid waste. Accordingly, wastewater-based sampling could miss between 10-20% of patients in general hospital patients ( Condon et al, 2019 ; Toba et al, 1996 ). This proportion is expected to be even higher in intensive care units where immobilization necessitated through ventilatory support further heightens toileting assistance requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, these sick and often elderly individuals are dependent on continence aids, adult diapers, sanitary pads and nursing cleanup; this results in fecal matter from these individuals being disposed into biohazard solid waste. Accordingly, wastewater-based sampling could miss between 10-20% of patients in general hospital patients[34, 35]. This proportion is expected to be even higher in ICU where immobilization necessitated through ventilatory support further heightens toileting assistance requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Given the focus of the study was on incontinence, associations with frailty were not fully explored, however, increased frailty scores were associated with both increased urinary and faecal incontinence. 29 Despite the difference in location (ie, New Zealand vs Ireland), these two studies suggest that approximately half of all inpatients within public hospitals are frail. However, the prevalence of frailty across all patients within an Australian hospital and within a private hospital setting has not previously been examined.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of frailty was found to increase significantly with age and differences were found between admission types (eg, patients admitted to a medical specialty were frailer than those admitted to a surgical specialty 12 ). Condon et al 29 assessed frailty using the Clinical Frail Scale 30 and reported 52.2% prevalence of frailty in an acute university hospital in Ireland. Given the focus of the study was on incontinence, associations with frailty were not fully explored, however, increased frailty scores were associated with both increased urinary and faecal incontinence.…”
Section: Introductionmentioning
confidence: 99%